2019
DOI: 10.1038/s41598-018-36537-3
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the right temporoparietal junction, but not lateral prefrontal or insular cortex, amplifies the role of goal-directed attention

Abstract: Whether an object captures attention depends on the interplay between its saliency and current behavioral predispositions of the observer. Neuroimaging work has implied a ventral attention network, comprising the temporoparietal junction (TPJ), lateral prefrontal cortex (lPFC) and the insula, in attentional orienting toward salient events. Activity of the TPJ is driven by novel and unexpected objects, while the lateral prefrontal cortex is involved in stimulus-driven as well as goal-directed processing. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…24 Finally, clusters of lower and higher RS FC were detected in the right supramarginal gyrus and right angular gyrus, implying a dysregulation within areas orienting attention toward task-relevant salient stimuli. 32 Moving to structural MRI analysis, we used DT tractography to quantify microstructural damage in several WM tracts with a well-known role for cognitive processes, including EF. In line with previous studies, the majority of the WM tracts analyzed showed significant FA reduction in MS patients compared to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…24 Finally, clusters of lower and higher RS FC were detected in the right supramarginal gyrus and right angular gyrus, implying a dysregulation within areas orienting attention toward task-relevant salient stimuli. 32 Moving to structural MRI analysis, we used DT tractography to quantify microstructural damage in several WM tracts with a well-known role for cognitive processes, including EF. In line with previous studies, the majority of the WM tracts analyzed showed significant FA reduction in MS patients compared to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed that this region acts as a "switch" that biases or interrupts ongoing cortical activity to redirect attention toward stimuli that threaten homeostasis (Menon and Uddin, 2010;Uddin, 2015). Although lesion evidence supports a specialization of the insula for bodily awareness rather than attention for external stimuli (Jones et al, 2010;Pedrazzini and Ptak, 2019), some studies noted that insular damage might contribute to spatial neglect (Golay et al, 2008;Molenberghs et al, 2012). The fact that the present study only found involvement of the right insula when cancellation performance was measured suggests a specific contribution of this region to spatial exploration, but not to object-based measures, such as reading or line bisection.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral studies with brain-damaged patients regularly report dissociations of performance in different tests of spatial attention, a finding reflecting the involvement of discrete cognitive mechanisms. For example, damage to posterior and inferior parietal or premotor cortex differently affects cancellation and line bisection (Pedrazzini et al, 2017;Toba et al, 2017), personal and extrapersonal space (Committeri et al, 2007;Baas et al, 2011), orienting of attention (Molenberghs et al, 2008;Vandenberghe et al, 2012;Pedrazzini and Ptak, 2019), and reading (Lee et al, 2009;Medina et al, 2009). Here, we examined whether such distinct patterns of performance in tests of spatial cognition are predictable from resting-state FC.…”
Section: Introductionmentioning
confidence: 99%
“…A spatial cuing task with different types of cues was employed to test participants' speed of orienting toward a target following a peripheral cue (Pedrazzini and Ptak 2019). All stimuli were composed of two 1° × 3° bars presented in a parallel (cues; horizontal bars separated by 4.5°) or perpendicular arrangement (targets and distracters; bars forming an L-or T-shape, presented at orientations 0°, 90°, 180° or 270°; Fig.…”
Section: Spatial Attention Taskmentioning
confidence: 99%